PENGARUH KEPEMIMPINAN, KEDISIPLINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN SELONG KABUPATEN LOMBOK TIMUR - Athar, Handry Sudiartha (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose-The purpose of this study was to analyze the influence of leadership, discipline and work environment on the performance of the Selong District Office staff in East Lombok Regency. Design/methodology/approach- Discrete research approach, a population of 32 people who were determined using census techniques. Analysis using Multiple Linear Regression, Hypothesis testing is done using partial test (t-test), simultaneous test (F-test) and coefficient of determination test (r2) Findings-Based on the results of an analysis of research shows that leadership variables have a positive and significant effect on employee performance with. Disciplinary variables have a significant positive effect on employee performance. Work environment variables have a positive and significant impact on employee performance. Simultaneously the three independent variables, leadership, discipline and work environment together have a significant positive effect on employee performance variables. Implications- The test results show that both the physical and non-physical environment has a positive and significant effect on employee performance. The implication is, office and room conditions must be considered if you want to improve the performance of Selong District Office employees Keywords:Leadership, Discipline, Work Environment, Employee Performance